Perancangan Sistem Presensi Permakanan Taruna Menggunakan Kartu RFID Berbasis Internet of Things - Toni Toni; Suse Lamtiar; Moch Faisal Yoga; Nawang Kalbuana (Departement of Mathematics Education, 2024)
This research aims to design and implement an RFID-based attendance system utilizing the Internet of Things (IoT) in the cadets dining hall of the Politeknik Penerbangan Indonesia Curug (PPI Curug). Employing the Research and Development (R&D) methodology adapted from Sugiyono, the study successfully integrated unique identification data (UID) from 8 RFID cards into the MySQL database and local web interface. Trial results demonstrate the system's success in accurately recording and managing the attendance data of the cadets. The local web interface provides an intuitive user access for monitoring attendance, while the data export feature enhances flexibility in managing cadets attendance information. Overall, the implementation of this system effectively combines RFID technology with the MySQL database and local web interface, forming a responsive solution for the management of cadets attendance within the campus environment. This system holds potential as a foundation for further development to enhance the efficiency of attendance recording in higher education institutions.